THE MEDIATING ROLE OF HR CAPABILITY IN THE RELATIONSHIP BETWEEN HR RESEARCH UTILIZATION AND ORGANIZATIONAL PERFORMANCE - Yuslim Yuslim; Alum Kusumah; Sulistyandari; Khusnul Fikri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study examines how HR research utilization affects organizational performance and tests whether HR capability mediates this relationship in an emerging economy context. Using a quantitative, cross sectional survey, data were collected from 220 HR professionals and senior managers involved in strategic HR decision making across organizations in Indonesia. The hypothesized model was analyzed using Partial Least Squares Structural Equation Modeling to estimate direct and indirect effects. Findings show that HR research utilization positively and significantly strengthens HR capability, and HR capability, in turn, positively influences organizational performance. The direct effect of HR research utilization on organizational performance is present but relatively weak. Mediation results confirm that HR capability significantly transmits the effect of research utilization to performance outcomes. Practically, the study suggests that organizations should not depend only on accessing or using HR research to improve results. Instead, they should invest in building HR capability, including analytical, professional, and strategic competencies, to translate research based knowledge into effective practices and measurable performance gains. The study advances evidence based HRM by showing that the research practice gap is primarily a capability development challenge rather than a knowledge access problem in emerging economy settings.